2020
DOI: 10.1177/2327857920091012
|View full text |Cite
|
Sign up to set email alerts
|

Informing the Design of Mental Health Smartphone Apps for Adolescents

Abstract: The purpose of this work is to obtain a set of best practices for the design of mental health smartphone applications (MHSAs) for an adolescent user base. The authors carried out a systematic literature review combined with a bibliographic coupling analysis to identify relevant literature, and then a thematic analysis of the literature to identify core principles. These efforts led to a framework of nine general principles for the creation and design of MHSAs. The nine core principles identified were: Using ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Yet, one recent comprehensive study showed that vendors vary significantly in the quality of their UCD practices, ranging from well-developed UCD processes to fundamental misconceptions of the UCD process [ 8 ]. Several studies included in this synthesis addressed the value of following a user- or human-centered design approach broadly, either conducting UCD or HCD in their own work or noting the importance of these approaches in health informatics design [ 2 , 7 8 9 10 11 12 13 14 15 16 17 ]. However, for the reasons above, readers of HF/E-focused health informatics manuscripts should be careful to interpret the authors’ use of the (often confused) terms HCD and UCD, and not assume their design process is of high quality.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, one recent comprehensive study showed that vendors vary significantly in the quality of their UCD practices, ranging from well-developed UCD processes to fundamental misconceptions of the UCD process [ 8 ]. Several studies included in this synthesis addressed the value of following a user- or human-centered design approach broadly, either conducting UCD or HCD in their own work or noting the importance of these approaches in health informatics design [ 2 , 7 8 9 10 11 12 13 14 15 16 17 ]. However, for the reasons above, readers of HF/E-focused health informatics manuscripts should be careful to interpret the authors’ use of the (often confused) terms HCD and UCD, and not assume their design process is of high quality.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies focused on creating and evaluating mobile apps, typically aimed at addressing the needs of patients and consumers. These mobile apps focused on a variety of chronic diseases such as diabetes and hypertension [ 63 , 122 ], cardiovascular health [ 30 , 58 , 121 ], cancer care [ 58 , 127 ], mental health [ 13 , 23 , 25 , 57 , 110 ], seizure management [ 57 ], bladder monitoring [ 56 ], tuberculosis treatment [ 15 ], and parental education [ 40 , 41 ]. A small number of studies focused on telehealth [ 10 , 14 , 140 ] and personal health records or patient portals [ 38 , 109 , 141 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation